READING MATERIAL MODEL WITH MULTICULTURAL CONTENT AS AN EFFORT TO FOSTER READING SKILL IN ELEMENTARY SCHOOL - -, Salimudin (The Journal of Educational Development, 2015)
The background of this study is the importance of reading as one of the most important skills to be mastered by students. However, the reality shows that the reading skill of Indonesian students is still poor as compared to the other countries. The study also reveals that Indonesia still encounters the unavailability of reading material with appropriate multicultural content. Therefore, the study aims to produce reading materials with multicultural content. The study employed R & D approach to conduct research, develop, and test the product. The results of field tests using t-test shows that the part 1 mean score output of Paired Samples Statistics on reading before the treatment is 65.17, and after using the developed reading material is 82,85. The part 2 output of Paired Samples Correlations shows that correlation value of two variables is 0.564 and the significance value is 0.00. The significance value of 0.00 is less than 0.05. The section 3 output of Paired Samples Test shows the value of 0.00 which is less than 0.05. The Paired Samples Test 0.00 value is less than 0.05. The value suggests that reading scores before and after using the developed material is different. The conclusion of this study is that there is a very significant difference between studentsâ reading skill before and after using the model of reading materials with multicultural content. Therefore, the model is able to effectively improve the studentsâ reading skill.